The civilization of Europe in the Renaissance - Hale, J. R. (Atheneum, 1994)
Exploring every aspect of art, philosophy, politics, life and culture between 1450 and 1620, this enthralling panorama examines one of the most fascinating and exciting periods in European history. "A rich, dense book which combines inspiring generalizations with idiosyncratic detail"